Emojurnalism dalam Ekosistem Media Digital - Desiana Desiana (Lembaga Pengembangan Kinerja Dosen, 2025)
The digital transformation of journalism has reshaped how news is communicated and consumed. In an ecosystem dominated by visual content and rapid engagement, emoji have emerged as essential tools for conveying emotional tone, shaping narratives, and enhancing audience interaction. This phenomenon is referred to as emojournalism, the use of emoji within journalistic content to foster emotional resonance and public engagement. This study employs a qualitative approach with a constructivist paradigm and phenomenological strategy. Data were collected through in-depth interviews, netnographic observation, and content analysis of online news shared on platforms like Instagram and Twitter. The analysis utilized Roland Barthes’ semiotic framework, supported by triangulation techniques to ensure data validity. Emoji function as emotional signifiers in news content, influencing audience interpretation and increasing digital interaction. Specific emojis—such as